2017
DOI: 10.1007/s40258-017-0350-x
|View full text |Cite|
|
Sign up to set email alerts
|

Dutch Economic Value of Radium-223 in Metastatic Castration-Resistant Prostate Cancer

Abstract: BackgroundThe treatment of metastatic castration-resistant prostate cancer has changed with the introduction of radium-223, cabazitaxel, abiraterone and enzalutamide. To assess value for money, their cost effectiveness in patients with metastatic castration-resistant prostate cancer previously treated with docetaxel from the Dutch societal perspective was investigated.MethodsA cost-effectiveness analysis was conducted using efficacy, symptomatic skeletal-related event and safety data obtained from indirect tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…The reviewed studies fulfilled 83.3% [22] and 87.5% [23,24] of CHEERS statement checklist. The studies generally represented a good quality.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The reviewed studies fulfilled 83.3% [22] and 87.5% [23,24] of CHEERS statement checklist. The studies generally represented a good quality.…”
Section: Resultsmentioning
confidence: 99%
“…A study by Peters et al [23] showed that cabazitaxel dominated abiraterone acetate, whereas studies by Wilson L. et al and Zhong L. et al revealed cabazitaxel as costlier and more effective than abiraterone acetate. Moreover, the ICER values of $337,983.33 /QALY and $918,166.67/QALY were far above the costeffectiveness threshold of the US.…”
Section: Cabazitaxel Versus Abiraterone Acetatementioning
confidence: 99%
See 3 more Smart Citations